National medical service
1943-10-20 1943 1940s 15 pages -8- students get through the closing net by the guile of professing to aim at the University degree and then in subsequent years branching off to the less valued qualification. Yet the public have little knowledge of any differential value between diplomas and degrees. The post-graduate specialists are only indicated by diplomas. There is no accredited evidence that the lay management boards of voluntary hospitals have demonstrated any superior talents for hospital administration than the Hospital Committees of Local Authorities, though the classes from which membership are drawn can be contrasted. Few nobles or rich business men seek co-option on to the Hospital Committee of Local Authorities. In Voluntary Hospitals there is a Medical Advisory Committee chosen by the consultant staff to act and even to sit with the Lay Committee, and the whole-time Medical Superintendent (where one is appointed instead of a Lay Secretary) has much less power than in Local Authority Institutions. The voluntary hospital Lay Committees have never challenged the rights of either consultants or residents to publish medical articles in the medical press from special cases or experience in the hospital though the residents as juniors freely consult their senior consultants. In the Local Authority hospitals there is frequently a prohibition or bar to the publication of medical articles by medical officers except after the expressed (often written) approval of the Medical Superintendent or the L.A. Lay Committee. This procedure is looked on with intense professional disfavour. The present Government has publicly pledged itself to the retention of the voluntary hospital system. This is unfortunate and undesirable because there will never be a really unified hospital system in Great Britain with two different systems of hospital administration, on entirely different lines, one set being really private institutions, without the right of public enquiry over any unfortunate episode, the other set being public institutions. The voluntary hospital in return for increasing National financial aid may make concessions of permitting Government or communal representation on their Management Boards with the right of Government inspection and enquiry but on the attachment of the teaching Medical Schools to voluntary hospitals there will be no surrender. The impression created on students in schools are too valuable and lasting to be given up. But in many L.A. institutions, such as the L.C.C., all the facilities exist in grouped institutions for an excellent Medical School and for a long time, in subjects like infectious fevers which the voluntary hospitals do not cater for, the medical students are allowed to attend special necessary prescribed courses there. (ii) Local Authority Institutions The other type of hospital is the Municipal or Local Authority Hospital. Taken together they provide more hospital beds in institutions than the voluntary hospitals - about two-thirds to one-third. There is usually a full time Medical Superintendent, who sits with the Local Authority Hospital Committee. The Medical Officers are full-time, appointed till resignation or promotion and not for specified periods (say 6 months as in voluntary hospitals). Sometimes consultants attend by agreement for working sessions once or twice a week, on an agreed payment scale. There is no Medical Advisory Committee and the only way of approach to the Lay Committee is via the Medical Officer of Health or the Medical Superintendent. The conditions vary in different parts of the country but what is here written is the usual practice. The administration is representative, elected and democratic. The elected members vary in type and ability and differ in many respects 292/847/2/113